Application of Energy Efficiency Techniques While Using ICT Equipment - Pano, Marijon (European Journal of Economics and Business Studies, 2017)
Information and Communication Technology (ICT) devices and services are becoming more and more widespread in all aspects of human life. Computers and home office equipment represent one of the fastest growing categories of home energy use. While ICT equipment has become more energy efficient in recent years, computers, peripherals, and data centers still use significant amounts of energy, especially if they are left on constantly. The information and technology ecosystem now represents around 10 percent of the world’s electricity generation and it represents the largest area of potential energy savings, as well. Most of these devices now have power management features that allow them to enter standby or -sleep- mode during periods of inactivity but only a fraction of users, know about the potential energy savings features. The aim of this paper is to offer practical and actionable tips for saving energy with computers and home office equipment. I review and test the main opportunities, explain them in plain language, and provide practical tips for leading an initiative to increase ICT energy efficiency in order to cut energy consumption per unit in half – or more. This paper presents the survey conducted about ICT equipment energy use in four offices and in five residential buildings in Korça region, Albania. The users were advised to use some basic energy efficiency tips, and energy data were collected before and after the new practices. Experimental results show that the methods used for increasing efficiency were very effective and the electricity consumption was reduced to about 10 percent - 45 percent in offices and about 5 percent - 15 percent in residential buildings.